Blang Sentang Village Community's Understanding of Indonesian Sharia Bank - Nur Hidayah Pulungan; Elpina Yanti Hasibuan; Muhammad Lathief Ilhamy Nasution (Penerbit Jurnal Indonesia, 2022)
The main problems in this study are 1) how is the understanding of the people of Blang Sentang Village towards Islamic banks indonesia, 2) What efforts are made by Islamic banking in socializing Islamic banks to the public. The type used in this research is a qualitative research type. The results of the study indicate that the public's understanding of Islamic banks is still lacking. Thus, through the program created by the Islamic banking party, it can overcome the problems that exist in the community, namely the lack of understanding of the people of Blang Sentang Village about Islamic banks.